O cerco da escritura em Saramago: caligrafia das vozes portuguesa - Diniz, Madson Góis (2014)
The studies concerning orality have been re-dimensioned in the linguistic arena debate, departing from the traditional incipient structuralism vision, seeking new routes to categorize voices in its totality. This thesis, in accordance to ethno linguistic and applied linguisticperspective, is oriented towards such principle, bringing into discussion a reflection towards the oral and the written upon Portuguese writer José Saramago ́s literary work, re-thinking concepts such as memory, identity and scripture based on theorists Paul Zumthor, Walter Ong, Deleuze and Derrida, as much as placing speaking as a major component for individuals in the context of a nation and social relations.